Representations of Public Spaces and the Construction of Race in Yoko Tawada's "Bioskoop der Nacht". (April 2017) - Redlich, Jeremy
Abstract : Race is subtly present, though never actually named as such, in several of Yoko Tawada's texts as a means by which protagonists self‐identify and are identified. However, despite the prominence of dermal and racial tropes throughout her oeuvre, there has been little discussion in secondary scholarship on this ideologically provocative aspect of Tawada's work. To illustrate Tawada's highly critical engagement with, and deconstruction of, racialized identities, the following analysis focuses on the short story "Bioskoop der Nacht" through a theoretical lens informed by critical race theory, theories of racial performativity and critical whiteness studies. Specifically, I investigate how public spaces, like a public toilet and a segregated public bench, can be consequential in producing a subject's identification with a racial category, which over time sediments as a naturalized and normalized fact of nature that seemingly never required constituting in the first place.